Cos (tan-1 x)


Expert Answers

An illustration of the letter 'A' in a speech bubbles

`cos(tan^-1 x) = 1/sqrt(1+x^2)`

If you need to prove the identity, then here are the steps.

First we will assume that arctanx = A

==> tanA = x

But we know that tanA = `sinA/cosA ` = opposite side/adjacent side= `x/1` Then we can assume that we have aright angle triangle such that the sides are x and 1.

Then, the hypotenuse is `h= sqrt(1^2+x^2)= sqrt(1+x^2).`

Now we need to find `cos(tan^-1x)`

`cos(tan^-1 x) = cos(A) =(adjacent)/h = 1/sqrt(1+x^2)` ==> `cos(tan^-1 x) = 1/sqrt(1+x^2)`

See eNotes Ad-Free

Start your 48-hour free trial to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Get 48 Hours Free Access
Approved by eNotes Editorial